Single Cell Transcriptomic Analyses Reveal the Impact of bHLH Factors on Human Retinal Organoid Development - Zhang, Xiangmei; Mandric, Igor; Nguyen, Kevin H.; Nguyen, Thao T. T.; Pellegrini, Matteo; Grove, James C. R.; Barnes, Steven; Yang, Xian-Jie (Frontiers in Cell and Developmental Biology, 2021)
The developing retina expresses multiple bHLH transcription factors. Their precise functions and interactions in uncommitted retinal progenitors remain to be fully elucidated. Here, we investigate the roles of bHLH factors ATOH7 and Neurog2 in human ES cell-derived retinal organoids. Single cell transcriptome analyses identify three states of proliferating retinal progenitors: pre-neurogenic, neurogenic, and cell cycle-exiting progenitors. Each shows different expression profile of bHLH factors. The cell cycle-exiting progenitors feed into a postmitotic heterozygous neuroblast pool that gives rise to early born neuronal lineages. Elevating ATOH7 or Neurog2 expression accelerates the transition from the pre-neurogenic to the neurogenic state, and expands the exiting progenitor and neuroblast populations. In addition, ATOH7 and Neurog2 significantly, yet differentially, enhance retinal ganglion cell and cone photoreceptor production. Moreover, single cell transcriptome analyses reveal that ATOH7 and Neurog2 assert positive autoregulation, suppress key bHLH factors associated with the neurogenic progenitors, and elevate bHLH factors expressed by exiting progenitors and differentiating neuroblasts. This study thus provides novel insight regarding how ATOH7 and Neurog2 impact human retinal progenitor behaviors and neuroblast fate choices.